THE SOIL’S DEGRADATION IN THE MICROBASIN OF THE MAIOR RIVER, URUSSANGA-SC - Vicente Rocha Silva (Sociedade & Natureza)
The southern region of Santa Catarina has been the subject of academic research since the nineties. A majority are related to the exploration of coal mines and its implication on the environmental degradation of the soils and hydric resources. The microbasin of the Maior River does not have favorable conditions for coal deposit to occur, even though it is included in the Geomorphologic Depressed Unit of the Carboniferous Zone of Santa Catarina. In this way, the deterioration of the in the Maior river is product of the relation between the society and nature. The an tropical alterations in the natural environment occurs in accordance with the physical characteristics of the place (climate, relief, vegetation, soil, as well as the sociocultural level, technological capacity and the economic resources of the population (Ross,1992). It is in the natural environments where the human societies structure themselves; extract the resources for survival and organization of physical territorial space (op.cit). The environmental deterioration in the micro-basin of the Maior River has direct relation to the occupation and use of the land for cultural purposes since the end of the nineteenth century. The colonization of the region began with the establishment of a headquarters for the colony of Urussanga, on May 26th 1878 (Escaravaco, 1984). The residing population at Maior River is predominantly 3rd to 5th generation Italian descendants. The microbasin of the Maior River has two sites: The Maior river line and the Maior River. The first immigrants came from the mountainous region of northern Italy (Escaravaco, 1984).